PROCESSING OF STEEL AND CAST IRON SCRAPS AT RUP “MAZ” - P. S. Gurchenko; M. I. Demin; A. I. Mihluk; A. M. Skibaij (Литьë и металлургия, 2007)
The original method of thermal cleaning of metal chips using high-frequency electromagnetic field was tested on the results of the carried out experimental- research works.